Australian political lives : chronicling political careers and administrative histories - Nethercote, J. R. (ANSOG monographs., 2006)
"This monograph brings together some of the best practitioners of the art and craft of political biography in Australia. They are simultaneously some of our best scholars who, at least in part, have turned their attention to writing Australian political lives. They are not merely chroniclers of our times but multidisciplinary analysts constructing layers of explanation and theoretical insight. They include academic, professional and amateur biographers; scholars from a range of disciplines (politics, history, sociology, public administration, gender studies); and politicians who for a time strutted the political stage. The assembled papers explore the strengths and weaknesses of the biographical approach; the enjoyment it can deliver; the problems and frustrations of writing biographies; and the various ways the 'project' can be approached by those constructing these lives. They probe the art and craft of the political biographer."--Publisher's description